Advances in Wood Preservation Technology: A Review of Conventional and Nanotechnology Preservation Approaches - Zhexun Ong; Mohammad Nasir Mat Arip; Shahlinney Lipeh Lipeh; Arnaud Besserer; Nicolas Brosse; Emmanuel Fredon; G. Veera Singham; Kah Hay Yuen; Hooi Ling Lee (BioResources, 2025)
While wood has been a renewable and versatile material for centuries, its susceptibility to biotic and abiotic degradation remains challenging. Traditional preservation methods, though effective, raise increasing concerns about environmental and health toxicity, cost, and post-consumer fate of the treated wood products. To address these issues, more sustainable and effective preservation methods have emerged. This review examines the latest innovations, particularly nanotechnology and self-emulsifying drug delivery systems (SEDDS), highlighting their applications, advantages, challenges, and research gaps. It focuses on literature from 2019 to 2024, exploring advancements in wood preservation. It also discusses the potential of these technologies to revolutionize wood preservation, offering promising and innovative solutions for the future.